K(ATP) channels process nucleotide signals in muscle thermogenic response - Reyes, Santiago (Crit Rev Biochem Mol Biol, 2010)
Uniquely gated by intracellular adenine nucleotides, sarcolemmal ATP-sensitive K(+) (K(ATP)) channels have been typically assigned to protective cellular responses under severe energy insults. More recently, K(ATP) channels have been instituted in the continuous control of muscle energy expenditure under non-stressed, physiological states. These advances raised the question of how K(ATP) channels can process trends in cellular energetics within a milieu where each metabolic system is set to buffer nucleotide pools. Unveiling the mechanistic basis of the K(ATP) channel-driven thermogenic response in muscles thus invites the concepts of intracellular compartmentalization of energy and proteins, along with nucleotide signaling over diffusion barriers. Furthermore, it requires gaining insight into the properties of reversibility of intrinsic ATPase activity associated with K(ATP) channel complexes. Notwithstanding the operational paradigm, the homeostatic role of sarcolemmal K(ATP) channels can be now broadened to a wider range of environmental cues affecting metabolic well-being. In this way, under conditions of energy deficit such as ischemic insult or adrenergic stress, the operation of K(ATP) channel complexes would result in protective energy saving, safeguarding muscle performance and integrity. Under energy surplus, downregulation of K(ATP) channel function may find potential implications in conditions of energy imbalance linked to obesity, cold intolerance and associated metabolic disorders.